Modeling and experiment on microstructure evolutions and mechanical properties in grade 600 MPa reinforcing steel rebar subjected to TempCore process - Bandyopadhyay, Kaushik; Lee, Joonho; Shim, Jae-Hyeok; Hwang, Byoungchul; Lee, Myoung-Gyu (ELSEVIER SCIENCE SA, 2019)
In this study, finite element (FE) modeling of the microstructure evolutions and resultant mechanical properties in the grade 600 MPa steel bar subjected to the TempCore process, a thermo-mechanically controlled process involving quenching and self-tempering, and related experiments are presented. The phase transformation kinetics based on the Johnson-Mehl-Avrami-Kolmogorov (JMAK) and Koistinen-Marburger equations were implemented in the user-defined subroutine of FE software to consider diffusional and martensitic transformations, respectively. Moreover, a robust simulation approach for solving complex thermo-mechanical problems induced by the quenching (i.e., external water cooling), internally generated heat due to phase transformations, and heat transfers between core and surface were addressed. The developed model can also simulate deformations associated with temperature change, phase transformations, and mechanical plasticity. The developed model was validated by estimating evolutions of various phase fractions and hardness in steel bars produced by both TempCore and normal air-cooling, which were compared with corresponding experimental results. Finally, prediction of flow stress curves and their experimental validation were also performed.
Keywords: HEAT-TRANSFER COEFFICIENT; PHASE-TRANSFORMATION; QUENCHING PROCESS; FEM SIMULATION; CARBON-STEEL; PREDICTION; AUSTENITE; BEHAVIOR; HARDNESS; MARTENSITE